The Influence of Video Media on The Skills and Creativity of Prosthetic Makeup for Character Venom Among 12th Grade Students At Vocational School - Lulu, Zinat; Kusmiyati, Kusmiyati (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2024)
This study aims to determine the effect of video media on the skills and creativity of beauty students. The research design used is an experimental approach with a quantitative method. The total population for this study comprised 54 students from two different classes, with 27 students in the control class and 27 in the experimental class. Data analysis involved percentage analysis, prerequisite tests, T-tests, and linear regression to identify differences in the dependent variable (Y) between the control and experimental classes and to determine the impact of the independent variable (X) on the dependent variable (Y). Results from the prerequisite tests, T-tests, and linear regression were obtained using the SPSS version 2.1 application. The sequence of tests concluded with the T-test on skills, revealing a significance value (sig) of 0.000 < 0.05, indicating differences in skills between the control and experimental classes. The T-test on creativity yielded a sig value of 0.000 < 0.05, signifying a difference in creativity between the two classes. The linear regression test resulted in a sig value of 0.000 < 0.05, indicating an influence of video media on students' skills and creativity. This overall analysis demonstrates a significant impact of video media on the skills and creativity of beauty students at SMKN 8 Surabaya.